Vigor and skill in the acrobatic mating displays of a Neotropical songbird. (20th September 2016) - Manica, Lilian T.; Macedo, Regina H.; Graves, Jeff A.; Podos, Jeffrey
Lay Summary: Males of many species push their physical capabilities to the limit as they display for females. In a Neotropical bird exhibiting "leap displays, " we show that costs of displays are higher for signalers of lower body mass, because they cannot conduct leaps that are both rapidly repeated and high in performance. Abstract : Animal social behaviors are often mediated by signals that provide information about signaler attributes. Although some signals are structurally simple, others are temporally dynamic and multifaceted. In such cases, exaggeration of some display components is likely to curtail the expression of others. We quantified features of the acrobatic, multimodal "leap display" of blue-black grassquits ( Volatinia jacarina ), which appears to entail moderate-to-high performance levels in terms of vigor and skill. We video recorded and quantified leap parameters (height, duration, rotation angle, launch velocity, and number of wing beats) and assessed how these parameters covaried with each other and with vocal parameters, display rates, and body mass index. Our analyses revealed correlations among multiple performance variables: leap height, duration, launch velocity, and number of wing beats. Leap height also correlated positively with song duration. By contrast, no leap parameters covaried with rotation angle. Our analyses also revealed a trade-off in vigor and skill-based leap attributes: birds with a lower body mass index showed a negative relationship between leap heights and the proportion of displays that included leaps (vs. perched vocalizations only). Our results identify directions of display evolution subject to mechanical or timing constraints and provide evidence that display attributes that emphasize vigor and skill may limit one another. Our results also support a key expectation of handicap models of display evolution, which is that costs of display execution should be borne disproportionately by signalers of lower quality.